Mountain lake responses to elevated nitrogen deposition in the West: algal productivity and nitrogen retention - Nydick, Koren Risa, author; Baron, Jill, advisor; Johnson, Brett, advisor; McKnight, Diane, committee member; Poff, LeRoy, committee member (Colorado State University. Libraries, 2002)
Atmospheric nitrogen (N) deposition is increasing in many regions of the western United States. The objective of this work was to understand how increased N deposition inputs alter algal productivity and N uptake in shallow mountain lake ecosystems. Effects of elevated N, in combination with added phosphorus (P) and increased acidity were investigated with enclosure experiments. A large dataset, the Western Lake Survey, was then used to estimate the percentage of western mountain lakes likely to experience the observed experimental changes.

Study lakes east of the Continental Divide in the Colorado Front Range had high nitrate (NO3) concentrations. Addition of NO3 to bottle bioassays never caused detectable increases in phytoplankton biomass, but combined N and P amendments almost always increased phvtoplankton biomass over controls. Larger enclosure experiments, which included benthic sediments and artificial tile substrates, yielded similar results. In contrast, study lakes in southern Wyoming had low NO3 concentrations and were N limited. Phytoplankton biomass and photosynthetic rate increased up to four-fold in response to NO3 amendments. Changes in phytoplankton community composition followed nutrient enrichment, but were more dramatic in response to increased acidity. Benthic algae rarely showed detectable changes in response to nutrients, alone or in combination with acid, but a 15N isotope tracer addition revealed that sediment dominated NO3 uptake. Sediment organic matter and carbon explained over two-thirds of the variability in sediment NO3 uptake, suggesting the importance of benthic microbial activity. These experiments showed that although phytoplankton were most sensitive to nutrient and acid additions, the benthos, and in particular, sediment microbial processes were likely the dominant regulator of ecosystem N uptake.

Using the Western Lake Survey, I estimated that 24% of mountain lakes without obvious land-based disturbances were N limited and likely would experience some degree of eutrophication from increased N input. Forty-eight percent of these lakes would not biologically buffer more than half of acid inputs from N deposition. Twelve percent also had very low measured alkalinities and were very acid sensitive. A substantial number of western lakes are likely to show some degree of observed experimental responses should N and acid inputs increase.
Keywords: ecology; biogeochemistry; environmental science; freshwater ecology; limnology